1996
DOI: 10.1136/jcp.49.3.213
|View full text |Cite
|
Sign up to set email alerts
|

Information on death certificates: cause for concern?

Abstract: Conclusions-Despite consistent encouragement to record all relevant details on death certificates this study shows that doctors fail to do so in most cases. Such a failure diminishes information available to the Office of Population Censuses and Surveys, affecting mortality statistics and gives further cause for concern about standards ofcertification. Means by which the standard of certification might be improved are discussed, including screening ofcertificates by a medically qualified person prior to regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 13 publications
3
20
0
1
Order By: Relevance
“…Much of the most important data is obtained from the stated cause of death, yet this is often noted to be faulty. 5,11,12 To improve accuracy of cause of death notation, some authors have suggested formal instruction in death certification during medical school and residency, 5 while others have suggested targeting of such instruction. 9,13 Our data support the notion of a general introduction for all physicians, with more detailed instruction directed toward particular specialists and fields of practice.…”
Section: Commentmentioning
confidence: 99%
“…Much of the most important data is obtained from the stated cause of death, yet this is often noted to be faulty. 5,11,12 To improve accuracy of cause of death notation, some authors have suggested formal instruction in death certification during medical school and residency, 5 while others have suggested targeting of such instruction. 9,13 Our data support the notion of a general introduction for all physicians, with more detailed instruction directed toward particular specialists and fields of practice.…”
Section: Commentmentioning
confidence: 99%
“…Although a published document from the Office of National Statistics (formerly the Office of Populations, Censuses, and Surveys) suggests that most "doctors are punctilious and precise in completing" certificates, 5 this fact has not been confirmed by previous studies. [6][7][8][9][10] In fact, it appears that certifying doctors have shown no improvement over the years to such a degree that authors would appear increasingly apathetic of this fact. 6 8 The Home Office has stated in its preliminary publication regarding its review of death certification that "looking again at the medical information sought on a death certificate might help address" the issue of poor performance.…”
mentioning
confidence: 99%
“…Not only will this alter vital statistics data but also changing the manner of death to accident could have financial benefits to the families with regard to various life insurance policies. As previous studies have demonstrated, the completion of death certificates is not always correct, even if tissue diagnosis are provided, [3][4][5][6][7] and is something that appears to be lacking in most medical school curriculum and residency teaching. 8,9 The investigators that communicate with the physicians feel that they do have some impact on teaching the physicians on how to recognize potential medical examiner cases (D.C.W., personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…In one study, only 23.6% of cases with an available tissue diagnosis actually listed that diagnosis as a cause of death. 7 The reason for this lack of accuracy in death certificates may be due to the medical education system. Maudsley and Williams 8 found that house officers in the UK felt undereducated in filling out death certificates, and Messite and Stellman 9 found similar problems for American internists, residents, and medical students.…”
mentioning
confidence: 99%